Effectiveness of a Guided Experimental Method for Increasing Learning Interest in Group B Children at Pertiwi Tluwuk Kindergarten - Febriyanti, Rahma Jihan; Mukminin, Amirul (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2025)
Interest in learning in early childhood classrooms can decline when instruction relies on passive routines and limited hands-on activity. This study examined whether a guided experimental activity could increase learning interest among Group B kindergarten children (5–6 years) at Pertiwi Tluwuk Kindergarten. Using a non-equivalent control-group quasi-experimental design (N = 45; experimental n = 22, control n = 23), the experimental group participated in a low-cost science activity (“bubble fizzy”), while the control group received conventional instruction. Learning interest was measured before and after the intervention through a structured oral assessment administered consistently across groups. Post-test scores were substantially higher in the experimental group (M = 19.45, SD = 2.92) than in the control group (M = 9.96, SD = 3.32), with a mean difference of 9.50 points, 95% CI [7.61, 11.38]. An independent-samples t test showed a significant group difference, t(43) = 10.16, p < .001, with a very large effect size (Hedges’ g = 2.97). The study contributes to the global early childhood literature by showing that short, guided, hands-on experiments can strengthen learning interest in resource-constrained kindergarten settings. Practically, the findings imply that teachers can use brief inquiry-based activities that combine child agency, immediate feedback, and observable cause-effect sequences to increase classroom engagement. However, interpretation remains limited by non-random class assignment, single-site implementation, and reliance on one assessment format. Future studies should use larger multi-site samples, baseline-adjusted analyses, and multimethod measures to test the durability and transferability of the effect across diverse pedagogical, cultural, and institutional contexts.